Population pharmacokinetics of iruplinalkib in healthy volunteers and patients with solid tumors - Guihong Yang; Yimei Wang; Huimin Zhao; Ziyi Jiang; Shansong Zheng; Mingjing Ge; Meimei Si; Xiaoyan Kang (Clinical and Translational Science)
Abstract Iruplinalkib (WX‐0593), a selective oral ALK/ROS1 tyrosine kinase inhibitor, was approved in China as first‐line therapy for ALK‐positive non‐small‐cell lung cancer (NSCLC) and for the treatment of locally advanced or metastatic ALK‐positive NSCLC that has progressed following crizotinib therapy. Pharmacokinetics (PK) data of iruplinalkib have been collected in healthy subjects and patient populations in several studies. We developed a population PK (PopPK) model for describing iruplinalkib plasma concentrations and for evaluating whether dose adjustments are necessary based on demographic factors or disease characteristics. Plasma concentration–time data were collected from 392 participants (16 healthy volunteers and 372 patients with solid tumors) who received single or multiple doses of iruplinalkib in four trials. Data were analyzed using non‐linear mixed‐effects modeling. Iruplinalkib plasma concentrations were best described by a two‐compartment model with first‐order absorption and first‐order elimination. Baseline body weight, time‐varying albumin, time‐varying creatinine clearance, and time‐varying lactate dehydrogenase were significant covariates of apparent clearance from the central compartment (CL/F) while baseline body weight was a significant covariate of apparent volume of the central compartment (V1/F). Given the small or modest effect of all statistically significant covariates on iruplinalkib exposure at steady‐state, no covariate was expected to have clinically meaningful effects on iruplinalkib exposure. Furthermore, iruplinalkib absorption was delayed 0.472 h after meal, and Ka was 58.8% of that under fasting. However, there was no difference in exposure of iruplinalkib between the fasted and fed states. In conclusion, the PopPK model adequately describes iruplinalkib PK properties in Chinese healthy subjects and patients with solid tumors. No covariate had a clinically meaningful impact on iruplinalkib exposure. These results indicate that dose adjustment of iruplinalkib is not necessary, based on the aforementioned covariates, for ALK‐positive NSCLC patients.